1997
DOI: 10.1023/a:1021958613125
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: 4-aminopyridine (4-AP) is a voltage-sensitive K(+)-channel blocker extensively used in in vitro experiments as a depolarizing agent for the release of glutamate (GLU). This research investigated whether 4-AP could be used in in vivo experiments using microdialysis. For that, the effects of 4-AP on the extracellular concentrations of glutamate (GLU), glutamine (GLN), taurine (TAU) and citrulline (CIT) in striatum of the freely moving rat were investigated. The effects of 4-AP were compared with those produced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…The percent increase in Glu was similar to that in previous work (see Table S-3 for comparison ,,,,,,, ). In addition, substantial effect of K + stimulation on GABA levels was also in agreement with the previous studies. ,, Increases in ACh were also similar to other previous reports. However, we observed increases in Gln, while other work reported decreases in Gln levels after K + stimulation. The reasons for this discrepancy are unclear. The other approaches perfused a high-K + solution for a much longer time.…”
Section: Resultssupporting
confidence: 92%
“…The percent increase in Glu was similar to that in previous work (see Table S-3 for comparison ,,,,,,, ). In addition, substantial effect of K + stimulation on GABA levels was also in agreement with the previous studies. ,, Increases in ACh were also similar to other previous reports. However, we observed increases in Gln, while other work reported decreases in Gln levels after K + stimulation. The reasons for this discrepancy are unclear. The other approaches perfused a high-K + solution for a much longer time.…”
Section: Resultssupporting
confidence: 92%
“…The concentration of Glu in many biological applications is low. For example, values reported under physiological conditions are normally below 10 μM for cerebrospinal fluid , and brain ECF, although 100 μM levels have been detected in the ECF following brain trauma . Thus, a critical property of GluOx-based biosensors is high sensitivity in the linear region, whereas with a solution K M (Glu) value of 0.2 mM, the range of linearity (up to 0.5 K M (Glu)) is not a major issue…”
Section: Resultsmentioning
confidence: 99%
“…We believed waiting six hr after probe insertion would be sufficient time to allow tissue to recover before baseline samples were collected. It has been demonstrated that extracellular glutamate levels stabilize following probe insertion after 3-4 hr (Yan et al 1998; Reznikov et al 2007), yet some research have measured basal levels immediately after probe insertion (Segovia et al 1997; Dahchour et al 1994). Further, mice had 24 hr access to EtOH the evening before, so it was crucial to not interrupt the heavy drinking.…”
Section: Methodsmentioning
confidence: 99%